To a question of architecture of psychotherapy systems - Курило, Віталій Олексійович (My University, 2018)
The task of the study was to analyze the problems of structuring a psychotherapeutic clinic and highlight the optimal structure of the stages of the psychotherapy system. To this end, a content analysis of existing ideas on the research topic was conducted. The results of the study demonstrate the state of psychotherapy as a clinical and scientific discipline in our time. The systematic use of contingent-specific combinations of psychotechnics determines the most relevant, at the moment, approach to structuring a psychotherapeutic clinic. Nevertheless, the issues of ergonomics and congruence both in relation to the object – the target contingent, and to the subject – the personality of the psychotherapist – receive the illumination only in separate studies. This list of conceptual studies sets is the general vector of methodological consolidation and disciplinary attribution of psychotherapy, transforming a disparate set of communicative practices, as it was at the beginning of the 21st century, into a clinical discipline that requires implementation of a systematic approach from the methodology that appeals to it. The study formulates the key questions, which are designed to determine the role and content of psychotherapy as a clinical discipline. The analysis of the existing systems of psychotherapy is carried out and their main features and global shortcomings are highlighted. The modern concept of the “psycho-phenomenological profile”, was designed to improve the psychotherapeutic process, was reviewed and analyzed. The optimal stages of the psychotherapy system and their components were highlighted. Завданням дослідження стало проаналізувати проблеми структурування психотерапевтичної клініки та виділити оптимальну структуру етапів системи психотерапії. З цією метою було проведено контент-аналіз існуючих уявлень з теми дослідження. Результати демонструють уявлення про стан психотерапії як клінічної та наукової дисципліни в наш час. Відзначено, що систематичне використання контингент-специфічних комбінацій психотехнік визначає найбільш актуальний на даний момент підхід до побудови психотерапевтичної клініки. Проте, питання ергономіки і конгруентності, як по відношенню до об'єкта – цільового контингенту, так і до суб'єкту – особистості психотерапевта висвітлюються тільки в окремих дослідженнях. Цей список концептуальних досліджень встановлює загальний вектор методологічної консолідації та дисциплінарної атрибуції психотерапії, перетворюючи розрізнений набір комунікативних практик, як це було на початку 21-го століття, в клінічну дисципліну, яка вимагає застосування системного підходу, заснованого на методології психотерапії. У дослідженні сформульовані ключові питання, які покликані визначити роль і зміст психотерапії як клінічної дисципліни. Проведено аналіз існуючих систем психотерапії та виділені їх основні риси і глобальні недоліки. Розглянуто та проаналізовано сучасну концепцію «психофеноменологічного профілю», яка покликана поліпшити психотерапевтичний процес. Виділено оптимальну структуру етапів системи психотерапії та їх компоненти. Задачей исследования стало проанализировать проблемы структурирования психотерапевтической клиники и выделить оптимальную структуру этапов системы психотерапии. С этой целью был проведен контент-анализ существующих представлений по теме исследования. Результаты исследования демонстрируют представление о состоянии психотерапии как клинической и научной дисциплины в наше время. Отмечено, что систематическое использование контингент-специфических комбинаций психотехник определяет наиболее актуальный на данный момент подход к построению психотерапевтической клиники. Тем не менее, вопросы эргономики и конгруэнтности как по отношению к объекту – целевому контингенту, так и к субъекту – личности психотерапевта освещаются только в отдельных исследованиях. Этот список концептуальных исследований устанавливает общий вектор методологической консолидации и дисциплинарной атрибуции психотерапии, превращая разрозненный набор коммуникативных практик, как это было в начале 21-го века, в клиническую дисциплину, которая требует применения системного подхода, основанного на методологии психотерапии. В исследовании сформулированы ключевые вопросы, которые призваны определить роль и содержание психотерапии как клинической дисциплины. Проведен анализ существующих систем психотерапии и выделены их основные черты и глобальные недостатки. Рассмотрена и проанализирована современная концепция «психофеноменологического профиля», призванная улучшить психотерапевтический процесс. Выделены оптимальные этапы системы психотерапии и их компоненты.
До питання про архітектуру систем психотерапії
К вопросу об архитектуре систем психотерапии
Keywords: psychotherapy; psycho-phenomenological profile; psychotechnics; stages of the system of psychotherapy; психотерапія; психофеноменологічний профіль; психотехніки; етапи системи психотерапії; психотерапия; психофеноменологический профиль; психотехники; этапы системы психотерапии